2014
DOI: 10.1007/s00063-014-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvante Therapie der Sepsis

Abstract: None of the new drugs, however, has successfully become established as a new standard of care. In the future, studies of novel sepsis therapies may succeed better if suitable biomarkers allow for patient selection, reflecting key pathophysiologic mechanisms that are targeted by the innovative drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Despite promising phase II studies, hardly any of these interventions could be shown to be beneficial in larger trials [3, 4]. This may be partly due to the fact that (i) circulating soluble biomarkers such as interleukin (IL)-1ß, tumor necrosis factor alpha (TNFα) and IL-6 indicating pro-inflammation have been readily accessible for many years and have been studied extensively [5], and (ii) it has only recently been shown that both pro- and anti-inflammatory activity occur concomitantly during sepsis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite promising phase II studies, hardly any of these interventions could be shown to be beneficial in larger trials [3, 4]. This may be partly due to the fact that (i) circulating soluble biomarkers such as interleukin (IL)-1ß, tumor necrosis factor alpha (TNFα) and IL-6 indicating pro-inflammation have been readily accessible for many years and have been studied extensively [5], and (ii) it has only recently been shown that both pro- and anti-inflammatory activity occur concomitantly during sepsis [6].…”
Section: Introductionmentioning
confidence: 99%